Social inequalities and access to health: challenges for society and the nursing field - Regina Celia Fiorati; Ricardo Alexandre Arcêncio; Larissa Barros de Souza (Universidade de São Paulo, 2016)
Objective to present a critical reflection upon the current and different interpretative models of the Social Determinants of Health and inequalities hindering access and the right to health. Method theoretical study using critical hermeneutics to acquire reconstructive understanding based on a dialectical relationship between the explanation and understanding of interpretative models of the social determinants of health and inequalities. Results interpretative models concerning the topic under study are classified. Three generations of interpretative models of the social determinants of health were identified and historically contextualized. The third and current generation presents a historical synthesis of the previous generations, including: neo-materialist theory, psychosocial theory, the theory of social capital, cultural-behavioral theory and the life course theory. Conclusion From dialectical reflection and social criticism emerge a discussion concerning the complementarity of the models of the social determinants of health and the need for a more comprehensive conception of the determinants to guide inter-sector actions to eradicate inequalities that hinder access to health.